The acceptance of shariah compliant on resort : a study of Perdana Resort,PCB Beach, Kelantan / Fasuriah Abd Wahab - Abd Wahab, Fasuriah (2012)
The researcher has conducted a study about “The Acceptance of Shariah Compliant on Resort: A Study of Perdana Resort, PCB Beach, Kelantan”. The aim of the study is to identify the factors in demanding to the acceptance of Shariah among the staff and guests of Perdana Resort and the researcher interest to know how acceptance of the principle at resort. The researcher has selected 100 respondents whose come from the staff and guests of Perdana Resort. The researcher was using Statistical Packages for the Social Science (SPSS) version 16.0 to analyzed the data in term of frequency, descriptive analysis, reliability analysis and multiple linear regression. The variables to encourage the acceptance of Shariah Compliant consist of acceptance as dependent variable and independent variables are service quality (operations), availability of the facilities (design and interiors), financial management and dealing with Non Muslims. The highest value in Mean is the acceptance at 6.880, followed by availability of the facilities (designs and interiors) at 6.8017. Next is dealing with Non Muslims at 6.7417, then the financial management at 6.6650 and the last is service quality (operations) at 6.5417. The result showed that staff and guests of Perdana Resort agree to adopt or accept the Shariah Compliant. By the way, the researcher likes to recommend several ideas regarding the acceptance of Shariah Compliant for the next coming soon study